(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The aim of the study was to demonstrate the extent to which the management of high involvement affects its dimensions (decision-making power, information acquisition, participation of returns, and knowledge ownership) by enhancing psychological capital by its dimensions. Self-efficiency, hope, optimism and flexibility.) of a sample(217) the teaching of those colleges. The researchers reached a number of conclusions, the most important of which is that it is possible to benefit from the mechanisms and dimensions of high containment management for the purpose of enhancing the psychological capital of the teachers in the faculties of the study sample. One of the most important recommendations of the study was the need for the faculties studied and benefiting from the experience to build an integrated model to implement the concepts of high containment management and to enhance the psychological capital when teaching.